Precursor containing primary particles distributed along radial direction and preparation method and application thereof

By controlling the co-precipitation reaction to prepare a core-shell structured lithium-ion battery precursor with radial distribution, the problems of volume expansion and cracking of cathode materials during cycling were solved, achieving efficient Li+ transport and improved electrochemical performance, and extending battery life.

CN121394347APending Publication Date: 2026-01-23JINGMEN GEM NEW MATERIAL CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511494378.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-20
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing lithium-ion battery cathode materials suffer from mechanical stress defects during charge-discharge cycles, leading to volume expansion and cracks, which affect Li+ and electron transport, reduce electrochemical performance, and cause rapid capacity decay due to core-shell structure mismatch.

Method used

By controlling the pH, ammonia concentration, and feed flow rate of the coprecipitation reaction, a precursor with a radially distributed core-shell structure is prepared. The outer shell is doped to form a loose outer shell to improve the bonding strength and uniformity. The dopant elements are uniformly distributed during the coprecipitation process to form a radially arranged structure to dissipate volume expansion stress. The outer shell acts as a 'safety cap' to prevent electrolyte penetration.

Benefits of technology

It improves the cycle and rate performance of lithium-ion battery cathode materials, suppresses microcrack formation, enhances Li+ transport efficiency, extends battery life, and inhibits side reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121394347A_ABST
    Figure CN121394347A_ABST
Patent Text Reader

Abstract

The invention provides a precursor containing primary particles distributed in the radial direction and a preparation method and application thereof.The preparation method comprises the steps that a mixed metal source solution, a complexing agent solution and a precipitator solution are subjected to a first coprecipitation reaction, and a core is obtained; in oxygen-free protective gas, increasing the flow of the mixed metal source solution, the complexing agent solution and the precipitator solution, and carrying out second coprecipitation reaction to obtain a core coated with a compact layer; in an oxygen-containing atmosphere, introducing the mixed metal source solution, the complexing agent solution, the precipitator solution and the doped metal source solution, and carrying out a third co-precipitation reaction to obtain a precursor; the pH and complexing agent concentration of the third co-precipitation reaction are smaller than those of the second co-precipitation reaction and are smaller than those of the first co-precipitation reaction. According to the preparation method, the precursor comprises the primary particles distributed along the radial direction by regulating and controlling the conditions of the coprecipitation reaction at each stage, so that the performances such as circulation and rate of the positive electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of batteries, and relates to a precursor containing primary particles distributed in a radial direction, and a preparation method and application thereof. BACKGROUND

[0002] Lithium-ion batteries are widely used in mobile devices and electric vehicles due to their high capacity, excellent energy density, and superior safety. With the rapid growth of electric vehicles, the market demand for higher energy density lithium-ion batteries has surged, driving the research and development of lithium-ion batteries. Despite the progress in lithium-ion battery technology, energy density remains a challenge to meet the range requirements of electric vehicle power batteries.

[0003] The capacity and energy density of lithium-ion batteries depend largely on the cathode, which accounts for 41% of the total weight of the battery. The cathode of commercial lithium-ion batteries has a lower capacity than the anode but is more expensive. Therefore, the existing technology mainly focuses on developing higher performance cathode materials. The first lithium-ion battery used LiCoO2 as the cathode, which has a low energy density (140-160 mAh / g) and a short cycle life. Moreover, due to the high cost of cobalt, LiCoO2 cathodes are not suitable for use in power batteries. Cobalt-free LiNiO2 cathodes have a very high reversible capacity (230-250 mAh / g), but are difficult to synthesize. With the pursuit of high-performance cathode materials, existing technology focuses on LiNi 1-x-y Co x Mn y O2 (NCM) derived materials. NCM includes a series of materials, including NCM111, NCM442, NCM622, and NCM811, etc., depending on the nickel content. High-nickel NCM cathodes (Ni content > 0.8) exhibit considerable energy density, such as NCM811 (about 200 mAh / g).

[0004] However, high-nickel NCM cathode materials still have drawbacks, the most notable of which is mechanical stress defects. During charge / discharge cycling, electrode particles undergo volume expansion / contraction, creating crack extensions from the inside of the particles to the particle surface, and the exposed active material surface reacts with the electrolyte, leading to electrolyte consumption and active material loss. At the same time, the cathode-electrolyte interface (CEI) formed by the side reaction hinders the transport of Li + and electrons, significantly reducing the electrochemical performance of the electrode particles.

[0005] To mitigate the mechanical stress-induced failure, researchers have made a large number of structural modifications to high-nickel NCM electrode particles, significantly improving the mechanical stability, and making the core-shell NCM electrode particles widely used. The core of the core-shell NCM electrode particle is made of high-nickel NCM material, such as NCM811, which provides high energy density, and the shell is low-nickel manganese-rich NCM material, such as NCM111, NCM622, etc., which improves the overall mechanical properties. Compared with single-core NCM particles, the shell of the core-shell NCM particle limits the core expansion during lithiation through its greater stiffness, thereby reducing the stress in the core, preventing the initiation and propagation of cracks, and showing better mechanical properties. Even so, the core-shell NCM particle still has the problem of structural mismatch between the core and the shell. The uneven volume shrinkage of the core and shell materials causes the core / shell interface to gradually debond and fail during cycling, and forms a gap of tens of nanometers, Li + and the electron transport is basically blocked, resulting in rapid capacity decay. At the same time, the interface debonding exposes the core material to the electrolyte in a large area, resulting in a large loss of active material and depletion of electrolyte.

[0006] Based on the above research, it is necessary to provide a preparation method of a precursor material, which has high matching degree between the core and the shell, regular radial arrangement of primary particles, and excellent doping effect, so as to improve the rate and cycle performance of the positive electrode material. SUMMARY

[0007] The purpose of the present application is to provide a precursor containing radially distributed primary particles and a preparation method and application thereof. The preparation method prepares a loose core first, then a dense layer, and finally a loose shell layer by adjusting the conditions of each stage of the coprecipitation reaction, so that the precursor includes radially distributed primary particles, which is beneficial to the transmission of Li + , and the combination between the layers is tight, the loose shell layer contains doping elements, and the cycle and rate performance of the positive electrode material is improved.

[0008] To achieve the purpose of the present application, the following technical solutions are adopted:

[0009] In a first aspect, the present application provides a preparation method of a precursor containing radially distributed primary particles, which comprises the following steps:

[0010] (1) introducing mixed metal source solution, complexing agent solution and precipitant solution into the bottom solution to carry out first coprecipitation reaction to obtain a core;

[0011] (2) in an oxygen-free protective gas, increasing the flow of the mixed metal source solution, the complexing agent solution and the precipitant solution to continue the second coprecipitation reaction to obtain a core coated with a dense layer;

[0012] (3) continuing to introduce the mixed metal source solution, the complexing agent solution, the precipitant solution and the doped metal source solution in an oxygen-containing atmosphere, continuing the third co-precipitation reaction to obtain the precursor, the precursor comprising primary particles distributed along a radial direction;

[0013] wherein the pH of the third co-precipitation reaction is less than the pH of the second co-precipitation reaction and less than the pH of the first co-precipitation reaction; the concentration of the complexing agent in the third co-precipitation reaction system is less than the concentration of the complexing agent in the second co-precipitation reaction system and less than the concentration of the complexing agent in the first co-precipitation reaction system.

[0014] The present application can obtain different layers by controlling the pH, ammonia concentration and feeding flow rate of each precipitation stage. Firstly, loose cores can be obtained by co-precipitation reaction under a feeding flow rate lower than that of step (2), a pH higher than that of step (3) and a complexing agent concentration higher than that of step (3). Then, the flow rates of the mixed metal source solution, the complexing agent solution and the precipitant solution are increased, and the reaction is continued in a non-oxygen-containing protective gas to obtain a dense layer on the surface of the core. Finally, the pH and the complexing agent concentration of the reaction are reduced, an oxygen-containing atmosphere is introduced, and the primary particles are distributed along a radial direction and have a loose shell layer. The primary particles distributed along a radial direction are beneficial to the transmission of Li + , and are beneficial to the rate capability and cycle performance.

[0015] Meanwhile, the shell layer is doped with a doping element, which is doped into the shell region that is in contact with the electrolyte and is prone to side reactions. The shell layer doping method is beneficial to the uniform distribution of the dopant in the co-precipitation synthesis process, and the doping effect can be maintained uniformly even in a large-scale synthesis process of the positive electrode material. In addition, the shell layer doping is beneficial to the formation of a radial arrangement after calcination, which is beneficial to the dispersion of stress caused by anisotropic volume expansion in the cycle process, significantly inhibits the formation of micro-cracks, and a spinel-like phase is formed on the surface of the particles, which is beneficial to the embedding and de-embedding of Li + , thereby improving the rate capability. In addition, the shell layer on the surface of the material is equivalent to a "safety cap", which can effectively prevent the penetration of the electrolyte and inhibit the occurrence of side reactions, thereby improving the cycle performance.

[0016] Preferably, the flow rate of the mixed metal source solution, the flow rate of the complexing agent solution and the flow rate of the precipitant solution are gradually increased during the period of 40-50% of the second co-precipitation reaction after the first co-precipitation reaction of step (1) is completed, for example, 40%, 42%, 44%, 46%, 48% or 50%.

[0017] Preferably, after the first co-precipitation reaction of step (1) is completed, to the stage of 40-50%, for example, 40%, 42%, 44%, 46%, 48% or 50%, of the second co-precipitation reaction, the flow rate of the mixed metal source solution is gradually increased to 4-6 L / h, for example, 4 L / h, 4.5 L / h, 5 L / h, 5.5 L / h or 6 L / h, the flow rate of the complexing agent solution is gradually increased to 300-500 mL / L, for example, 300 mL / L, 350 mL / L, 400 mL / L, 450 mL / L or 500 mL / L, and the flow rate of the precipitant solution is gradually increased to 1-2.5 L / h, for example, 1 L / h, 1.5 L / h, 2.0 L / h or 2.5 L / h, and then the second co-precipitation reaction is continued at the increased flow rates.

[0018] For example, after the first co-precipitation reaction of step (1) is completed, to the stage of 40% of the second co-precipitation reaction, the flow rate of the mixed metal source solution, the flow rate of the complexing agent solution and the flow rate of the precipitant solution are gradually increased to a fixed value within the above-mentioned ranges, and then the second co-precipitation reaction is continued at the fixed value.

[0019] Preferably, after the first co-precipitation reaction of step (1) is completed, to the stage of 40-50%, for example, 40%, 42%, 44%, 46%, 48% or 50%, of the second co-precipitation reaction, the pH of the system is gradually increased.

[0020] Preferably, after the first co-precipitation reaction of step (1) is completed, to the stage of 40-50%, for example, 40%, 42%, 44%, 46%, 48% or 50%, of the second co-precipitation reaction, the pH of the system is gradually increased to the range of 11.3-11.6, for example, 11.3, 11.4, 11.5 or 11.6, and then the second co-precipitation reaction is continued at the pH in the range of 11.3-11.6, for example, 11.3, 11.4, 11.5 or 11.6.

[0021] After the second co-precipitation reaction of step (2) is completed, to the stage of 40-50%, for example, 40%, 42%, 44%, 46%, 48% or 50%, of the third co-precipitation reaction, the pH of the system is gradually decreased.

[0022] Preferably, after the second co-precipitation reaction in step (2) ends, the third co-precipitation reaction is carried out to 40-50%, for example, it can be 40%, 42%, 44%, 46%, 48% or 50%, and the pH of the system is gradually reduced to 10.8-11, for example, it can be 10.8, 10.85, 10.9, 10.95 or 11, and then the third co-precipitation reaction is continued at a pH in the range of 10.8-11, for example, it can be 10.8, 10.85, 10.9, 10.95 or 11.

[0023] Preferably, after the second co-precipitation reaction in step (2) ends, the third co-precipitation reaction is carried out to 40-50%, for example, it can be 40%, 42%, 44%, 46%, 48% or 50%, and the complexing agent concentration of the system is gradually reduced.

[0024] Preferably, after the second co-precipitation reaction in step (2) ends, the third co-precipitation reaction is carried out to 40-50%, for example, it can be 40%, 42%, 44%, 46%, 48% or 50%, and the complexing agent concentration of the system is gradually reduced to 3-5 g / L, for example, it can be 3 g / L, 3.5 g / L, 4 g / L, 4.5 g / L or 5 g / L, and then the third co-precipitation reaction is continued at a complexing agent concentration of the system in the range of 3-5 g / L, for example, it can be 3 g / L, 3.5 g / L, 4 g / L, 4.5 g / L or 5 g / L.

[0025] The change of the reaction conditions at each stage of the present application is not a sudden change, but a gradual reduction or increase to the reaction conditions at that stage, achieving a gradient change rather than a sudden change in each layer, achieving a condition transition, thereby making the interface of each layer continuous, improving the bonding strength between each layer, reducing the difference in volume expansion between each layer, thereby further improving the stability of the positive electrode material and the performance of the battery.

[0026] Preferably, the ratio of the flow rates of air and protective gas introduced during the first co-precipitation reaction in step (1) is 0-0.2, for example, it can be 0, 0.05, 0.1, 0.15 or 0.2, and the protective gas includes nitrogen.

[0027] Preferably, the particle size D50 of the core in step (1) is 1.5-2 μm, for example, it can be 1.5 μm, 1.7 μm or 2 μm, but is not limited to the listed values, and other values not listed within the value range are also applicable.

[0028] Preferably, the pH of the first co-precipitation reaction of step (1) is in the range of 11-11.3, for example, it can be 11, 11.1, 11.2 or 11.3, and the complexing agent concentration is in the range of 5-7 g / L, for example, it can be 5 g / L, 5.5 g / L, 6 g / L, 6.5 g / L or 7 g / L, but is not limited to the listed values, and other values not listed in the value range are also applicable.

[0029] Preferably, the flow rate of the mixed metal source solution into the bottom liquid of step (1) is 1.5-3.5 L / h, for example, it can be 1.5 L / h, 2 L / h, 2.5 L / h, 3 L / h or 3.5 L / h, the flow rate of the complexing agent solution into the bottom liquid is 150-300 mL / L, for example, it can be 150 mL / L, 200 mL / L, 250 mL / L or 300 mL / L, and the flow rate of the precipitant solution into the bottom liquid is 0.5-1.5 L / h, for example, it can be 0.5 L / h, 0.75 L / h, 1 L / h, 1.25 L / h or 1.5 L / h, but is not limited to the listed values, and other values not listed in the value range are also applicable.

[0030] Preferably, the bottom liquid of step (1) comprises pure water, a precipitant and a complexing agent.

[0031] Preferably, the pH of the bottom liquid of step (1) is 10.8-11.3, for example, it can be 10.8, 10.9, 11, 11.1, 11.2 or 11.3, and the complexing agent concentration is 5-7 g / L, for example, it can be 5 g / L, 5.5 g / L, 6 g / L, 6.5 g / L or 7 g / L, but is not limited to the listed values, and other values not listed in the value range are also applicable.

[0032] In the present application, the pH of the bottom liquid and the concentration of the complexing agent are adjusted in the reaction device, and when the bottom liquid is heated to 50-80℃, N2 is also introduced, and the flow rate of the introduced N2 is 0.5-2 m 3 / h, for example, it can be 0.5 m 3 / h, 1 m 3 / h, 1.5 m 3 / h or 2 m 3 / h, but is not limited to the listed values, and other values not listed in the value range are also applicable.

[0033] Preferably, the total metal ion concentration in the mixed metal source solution of step (1), the mixed metal source solution of step (2) and the mixed metal source solution of step (3) is independently 80-200 g / L, for example, it can be 80 g / L, 100 g / L, 150 g / L or 200 g / L, but is not limited to the listed values, and other values not listed in the value range are also applicable.

[0034] Preferably, the molar ratio of Ni element, Co element and Mn element in the mixed metal source solution of step (1), the mixed metal source solution of step (2) and the mixed metal source solution of step (3) is independently (60-95):(0-15):(0-15), for example, it can be 70:15:15, 80:10:10, 90:5:5 or 95:2.5:2.5, but is not limited to the listed values, and other values not listed in the value range are also applicable.

[0035] Preferably, the mixed metal source solution of step (1), the mixed metal source solution of step (2) and the mixed metal source solution of step (3) are obtained by mixing a nickel source, a cobalt source and a manganese source with water, wherein the nickel source includes any one or a combination of at least two of nickel sulfate, nickel nitrate, nickel acetate or nickel chloride (preferably nickel sulfate), the cobalt source includes any one or a combination of at least two of cobalt sulfate, cobalt nitrate, cobalt acetate or cobalt chloride (preferably cobalt sulfate), and the manganese source includes any one or a combination of at least two of manganese sulfate, manganese nitrate, manganese acetate or manganese chloride (preferably manganese sulfate).

[0036] Preferably, the precipitant solvent of the present application includes a sodium hydroxide solution, and the complexing agent solution includes ammonia.

[0037] Preferably, the temperature of the first co-precipitation reaction of step (1), the second co-precipitation reaction of step (2) and the third co-precipitation reaction of step (3) is independently 50-80℃, for example, it can be 50℃, 60℃, 70℃ or 80℃, but is not limited to the listed values, and other values not listed in the value range are also applicable.

[0038] Preferably, the particle size D50 of the core of the coated dense layer of step (2) is 4-6μm, for example, it can be 4μm, 5μm or 6μm, but is not limited to the listed values, and other values not listed in the value range are also applicable.

[0039] Preferably, the oxygen-free protective gas of step (2) includes nitrogen.

[0040] Preferably, in the second co-precipitation reaction system of step (2), the concentration of the complexing agent is 5-7g / L, for example, it can be 5g / L, 5.5g / L, 6g / L, 6.5g / L or 7g / L, but is not limited to the listed values, and other values not listed in the value range are also applicable.

[0041] Preferably, in the doped metal source solution of step (3), the doped metal element includes any one or a combination of at least two of Al, Ti, Nb, Zr, W, V, Sr, Ga, Ce, Y, La, Sb or B, and is preferably W.

[0042] The preferred shell layer doping element is tungsten (tungsten source is tungsten pentachloride), and the W-doped shell formed on the surface is beneficial to forming a radial arrangement distribution structure after calcination, which is beneficial to dissipating the stress caused by anisotropic volume expansion in the circulation process, and significantly inhibits the formation of micro-cracks.

[0043] Preferably, in the co-precipitation reaction system of step (3), the doping metal element accounts for 0.05-5% of the total metal mole, for example, it can be 0.05%, 1%, 2%, 3%, 4% or 5%, but is not limited to the listed values, and other values not listed in the value range are also applicable, preferably 0.5-1%.

[0044] The proportion of the doping metal element will affect the performance of the material. If the content of the doping metal element is too low, the doping effect will decrease, and if the content of the doping metal element is too high, the transition metal ion sites occupied will also be more, and the discharge capacity of the material will be limited, and at the same time, the lattice distortion effect will also deteriorate the electrochemical performance.

[0045] Preferably, the concentration of the doping metal source solution in step (3) is 20-50 g / L, for example, it can be 20 g / L, 30 g / L, 40 g / L or 50 g / L, but is not limited to the listed values, and other values not listed in the value range are also applicable.

[0046] Preferably, the oxygen-containing atmosphere in step (3) includes air and protective gas with a flow ratio of 0.1-0.3, for example, it can be 0.1, 0.15, 0.2, 0.25 or 0.3, but is not limited to the listed values, and other values not listed in the value range are also applicable.

[0047] Preferably, in step (3), when the third co-precipitation reaction is carried out, the flow rate of the mixed metal source solution continuously introduced is 4-6 L / h, for example, it can be 4 L / h, 5 L / h or 6 L / h, the flow rate of the complexing agent solution is 300-500 mL / L, for example, it can be 300 mL / L, 350 mL / L, 400 mL / L, 450 mL / L or 500 mL / L, the flow rate of the precipitant solution is 1-2.5 L / h, for example, it can be 1 L / h, 1.5 L / h, 2 L / h or 2.5 L / h, and the flow rate of the doping metal source solution is 100-300 mL / h, for example, it can be 100 mL / h, 150 mL / h, 200 mL / h, 250 mL / h or 300 mL / h, but is not limited to the listed values, and other values not listed in the value range are also applicable.

[0048] Preferably, the third co-precipitation reaction in step (3) is performed until a target particle size D50 of 11-13 μm is reached, such as 11 μm, 11.5 μm, 12 μm, 12.5 μm or 13 μm, but not limited to the listed values, other values not listed within the range of values are also applicable.

[0049] Preferably, after the third co-precipitation reaction in step (3) is completed, aging, washing, drying and post-treatment are further performed, wherein the washing includes at least three times of washing with hot water and at least one time of washing with dilute alkali, and the drying temperature is 100-200 ℃, such as 100 ℃, 125 ℃, 150 ℃, 175 ℃ or 200 ℃, but not limited to the listed values, other values not listed within the range of values are also applicable.

[0050] Preferably, the chemical formula of the precursor is wherein 0.6

[0051] In a second aspect, the present application provides a precursor containing radially distributed primary particles, which is prepared by the preparation method as described in the first aspect.

[0052] The precursor containing radially distributed primary particles includes a core, a dense layer on the surface of the core, and a loose layer on the surface of the dense layer.

[0053] In a third aspect, the present application provides a positive electrode material, which is prepared by mixing a lithium source and the precursor containing radially distributed primary particles as described in the second aspect and sintering.

[0054] Preferably, the molar ratio of total metal ions in the precursor containing radially distributed primary particles to lithium ions in the lithium source is 1:(1.1-1.2), such as 1:1.1, 1:1.125, 1:1.15, 1:1.175 or 1:1.2, but not limited to the listed values, other values not listed within the range of values are also applicable.

[0055] Preferably, the sintering comprises a first sintering stage and a second sintering stage in sequence, wherein the first sintering stage has a temperature of 400-600°C, for example 400°C, 450°C, 500°C, 550°C or 600°C, a time of 4-6h, for example 4h, 4.5h, 5h, 5.5h or 6h, and a temperature rising speed of 2-5°C / min, for example 2°C / min, 3°C / min, 4°C / min or 5°C / min, and the second sintering stage has a temperature of 800-1100°C, for example 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C or 1100°C, a time of 8-15h, for example 8h, 9h, 10h, 11h, 12h, 13h, 14h or 15h, and a temperature rising speed of 4-8°C / min, for example 4°C / min, 5°C / min, 6°C / min, 7°C / min or 8°C / min, but is not limited to the listed values, and other values not listed in the range are also applicable.

[0056] In a fourth aspect, the present application provides a lithium ion battery comprising the positive electrode material according to the third aspect.

[0057] Compared with the prior art, the present application has the following beneficial effects:

[0058] (1) The present application can obtain different layers by controlling the pH, ammonia concentration and feed flow rate of each precipitation stage. Firstly, porous loose core can be obtained by co-precipitation reaction under a feed flow rate lower than that of step (2), a pH higher than that of step (3) and a complexing agent concentration higher than that of step (3). Then, a dense layer is obtained on the surface of the core by increasing the flow rates of the mixed metal source solution, the complexing agent solution and the precipitant solution and continuing the reaction in a non-oxygen-containing protective gas. Finally, a primary particle with a loose shell layer is obtained by reducing the reaction pH and the complexing agent concentration and introducing an oxygen-containing atmosphere. The radial distribution of the primary particle is beneficial to the transmission of Li + , and is beneficial to the rate performance and cycle performance.

[0059] (2) The present application also performs doping when the shell layer is prepared. The doping element is doped into the shell region which is in contact with the electrolyte and is prone to side reactions. The shell doping method is beneficial to the uniform distribution of the dopant in the co-precipitation synthesis process, and the uniformity of the doping effect can be maintained even in the large-scale synthesis of the positive electrode material. In addition, the shell doping is also beneficial to the formation of the radial distribution structure after calcination, which is beneficial to the dispersion of the stress caused by the anisotropic volume expansion in the cycle process, significantly inhibits the formation of micro-cracks, and a spinel-like phase is formed on the surface of the particle, which is beneficial to the transmission of Li +The embedding and de-embedding of the particles improves the rate performance. In addition, the shell layer on the surface of the material is equivalent to a "safety cap", which can effectively prevent the penetration of electrolyte and inhibit the occurrence of side reactions, thereby improving the cycle performance. BRIEF DESCRIPTION OF DRAWINGS

[0060] Figure 1 SEM image of the precursor obtained by the preparation method described in Embodiment 1 of the present application.

[0061] Figure 2 Cross-sectional image of the precursor obtained by the preparation method described in Embodiment 1 of the present application. DETAILED DESCRIPTION

[0062] The technical solutions of the present application will be further described below through specific embodiments. Those skilled in the art should understand that the embodiments are only used to help understand the present application and should not be regarded as specific limitations of the present application.

[0063] Embodiment 1

[0064] The present embodiment provides a preparation method of a precursor containing primary particles distributed in the radial direction, which comprises the following steps:

[0065] (1) A mixed ternary metal salt solution with a total concentration of metal elements of 150 g / L and a molar ratio of Ni, Co and Mn elements of 85:10:5 is prepared, a NaOH solution with a mass concentration of 18% is prepared, an ammonia water with a mass concentration of 8% is prepared, and a tungsten pentachloride solution with a concentration of 20 g / L is prepared as a doped metal W salt solution;

[0066] (2) Preparation of the base solution: 200 L of pure water and a certain amount of NaOH solution and ammonia water are added to a 300 L reaction kettle, and nitrogen gas is introduced into the base solution at a rate of 2 m 3 / h, and stirred at a speed of 300 r / min to make it uniform, then heated to 70℃, and the pH value of the base solution is controlled at 10.8-11.3, and the ammonia concentration is controlled in the range of 5-7 g / L;

[0067] (3) Coprecipitation reaction: control the reaction temperature to be 70℃, and the stirring speed to be 450 r / min, and then perform the following stage reaction: a. Internal loose core: flow the ammonia water, NaOH solution and mixed ternary metal salt solution into the reactor at the same time to perform the first coprecipitation reaction, open the air, and maintain the ratio of air flow to nitrogen flow at 0.1, and then when the internal nucleation is completed and the particle size D50 is to 1.5 μm, the core is obtained, and the first stage reaction is completed; b. Intermediate dense layer: in this reaction stage, the air is not passed through, the nitrogen is kept unobstructed, the flow of the ammonia water, NaOH solution and mixed ternary metal salt solution is increased, the ammonia water, NaOH solution and mixed ternary metal salt solution are flowed into the reactor at the same time to perform the second coprecipitation reaction, and when the particle size D50 is grown to 5 μm, the second stage reaction is completed; c. External loose layer: open the pump of the doped metal W salt solution, flow the ammonia water, NaOH solution, mixed ternary metal salt solution and doped metal W salt solution into the reactor at the same time to continue the third coprecipitation reaction, open the air, and maintain the ratio of air flow to nitrogen flow at 0.2, and then when the growth is to the target particle size D50 value of 12 μm, stop feeding the reaction;

[0068] In the first coprecipitation reaction stage of step (3), the flow rate of the mixed ternary metal salt solution is 2.5 L / h, the flow rate of the ammonia water is 200 mL / L, the flow rate of the NaOH solution is 1 L / h, the pH is controlled in the range of 11-11.3, and the ammonia is controlled in the range of 5-7 g / L; in the second coprecipitation reaction stage, the flow rate of the mixed ternary metal salt solution is 5 L / h, the flow rate of the ammonia water is 400 mL / L, the flow rate of the NaOH solution is 1.5 L / h, the pH is controlled in the range of 11.4-11.6, and the ammonia is controlled in the range of 5-7 g / L; in the third coprecipitation reaction stage, the flow rate of the mixed ternary metal salt solution is 5 L / h, the flow rate of the ammonia water is 400 mL / L, the flow rate of the NaOH solution is 1.5 L / h, the flow rate of the doped metal W salt solution is 200 mL / h, the pH is controlled in the range of 10.8-10.9, the ammonia is controlled in the range of 3-4.5 g / L, and the doping amount of tungsten accounts for 1% of the total molar percentage of the ternary Ni, Co and Mn elements;

[0069] (4) The obtained qualified slurry is washed and dried, wherein the washing is performed twice by alkali washing and three times by water washing, the drying temperature is 150℃, and the precursor containing the radially distributed primary particles is obtained, the SEM image of the precursor is shown in Figure 1 , the cross-sectional view is shown in Figure 2 , and it can be seen from Figure 1 that the primary particles are relatively loose and present as needles, Figure 2 and the relatively obvious radial distribution characteristics are observed in .

[0070] The embodiment also provides a preparation method of the positive electrode material.

[0071] The precursor prepared in step (4) of this example and a lithium source are put into a high-speed mixer for batch mixing to obtain a mixture, the molar ratio of the total amount of nickel element, cobalt element, manganese element and tungsten element contained in the precursor to the amount of lithium element contained in the lithium source is 1:1.2, and the mixture is subjected to secondary sintering in a box furnace, wherein the temperature of the first stage of calcination is 500°C, the time is 5h, the temperature of the second stage of calcination is 1200°C, and the time is 8h, and finally the positive electrode material is obtained.

[0072] Example 2

[0073] This example provides a preparation method of a precursor containing primary particles distributed in a radial direction, which comprises the following steps:

[0074] (1) A mixed ternary metal salt solution with a total concentration of metal elements of 150g / L and a molar ratio of Ni, Co and Mn elements of 85:10:5 is prepared, a NaOH solution with a mass concentration of 18% is prepared, an ammonia water with a mass concentration of 8% is prepared, and a tungsten pentachloride solution with a concentration of 20g / L is prepared as a doped metal W salt solution;

[0075] (2) Preparation of a base solution: 200L of pure water and a certain amount of NaOH solution and ammonia water are added to a 300L reaction kettle, nitrogen gas is introduced into the base solution at a rate of 2m 3 / h, stirring is carried out at a speed of 300r / min to make the mixture uniform, and then the temperature is raised to 70°C, the pH value of the base solution is controlled to be 10.8-11.3, and the ammonia concentration is controlled to be in the range of 5-7g / L;

[0076] (3) Co-precipitation reaction: the reaction temperature is controlled to be 70°C, the stirring speed is 450r / min, and the following stages of reaction are carried out: a. internal loose core: the ammonia water, NaOH solution and mixed ternary metal salt solution are simultaneously flowed into the reaction kettle for the first co-precipitation reaction, air is opened, the ratio of air flow to nitrogen flow is maintained at 0.1, and when the internal nucleation is completed and the particle size D50 is to 1.5μm, the core is obtained, and the first stage reaction is completed; b. intermediate dense layer: no air is introduced, nitrogen is kept flowing, the flow rates of ammonia water, NaOH solution and mixed ternary metal salt solution are increased, the ammonia water, NaOH solution and mixed ternary metal salt solution are simultaneously flowed into the reaction kettle for the second co-precipitation reaction, and when the particle size D50 grows to 5μm, the second stage reaction is completed; c. external loose layer: the doped metal W salt solution pump is opened, the ammonia water, NaOH solution, mixed ternary metal salt solution and doped metal W salt solution are simultaneously flowed into the reaction kettle for the third co-precipitation reaction, air is opened, the ratio of air flow to nitrogen flow is maintained at 0.2, and when the target particle size D50 value is 12μm, the feeding reaction is stopped;

[0077] The flow rate of the mixed ternary metal salt solution in the first co-precipitation reaction stage is 2.5 L / h, the flow rate of the ammonia water is 200 mL / L, the flow rate of the NaOH solution is 1 L / h, the pH is controlled in the range of 11-11.3, and the ammonia is controlled in the range of 5-7 g / L;

[0078] After the first co-precipitation reaction, to the stage of 45% of the second co-precipitation reaction, the flow rate of the mixed ternary metal salt solution is gradually increased to 5 L / h, the flow rate of the ammonia water is gradually increased to 400 mL / L, the flow rate of the NaOH solution is gradually increased to 1.5 L / h, the pH is gradually increased to 11.4-11.6, and the ammonia is controlled in the range of 5-7 g / L, and then the second co-precipitation reaction is continued under the conditions;

[0079] After the second co-precipitation reaction, to the stage of 45% of the third co-precipitation reaction, the pH is gradually decreased to 10.8-10.9, and the ammonia is gradually decreased to the range of 3-4.5 g / L, and the third co-precipitation reaction is continued under the conditions; the flow rate of the mixed ternary metal salt solution in the third co-precipitation reaction is 5 L / h, the flow rate of the ammonia water is 400 mL / L, the flow rate of the NaOH solution is 1.5 L / h, the flow rate of the doped metal W salt solution is 200 mL / h, and the doping amount of tungsten accounts for 1% of the total mole percentage of the ternary Ni, Co and Mn elements.

[0080] (4) The obtained qualified slurry is washed and dried, wherein the washing is performed twice by alkali washing and three times by water washing, the drying temperature is 150°C, and the precursor containing the radially distributed primary particles is obtained.

[0081] The embodiment also provides a preparation method of the positive electrode material, and the preparation method comprises the following steps:

[0082] The precursor prepared in step (4) of the embodiment and a lithium source are put into a high-speed mixer to obtain a mixture, the mole ratio of the total amount of nickel elements, cobalt elements, manganese elements and tungsten elements contained in the precursor to the lithium elements contained in the lithium source is 1:1.2, and the mixture is subjected to secondary sintering in a box furnace, wherein the temperature of the first stage of calcination is 500°C, the time is 5 h, the temperature of the second stage of calcination is 1200°C, and the time is 8 h, and finally the positive electrode material is obtained.

[0083] Embodiment 3

[0084] The embodiment provides a preparation method of a precursor containing radially distributed primary particles, and the preparation method comprises the following steps:

[0085] (1) Prepare a mixed ternary metal salt solution with a total concentration of metal elements of 80 g / L and a molar ratio of Ni, Co and Mn elements of 80:10:10, prepare a NaOH solution with a mass concentration of 18%, and prepare an ammonia water with a mass concentration of 8%, and prepare a tungsten pentachloride solution with a concentration of 35 g / L as a doped metal W salt solution;

[0086] (2) Prepare a base solution: add 200 L of pure water and a certain amount of NaOH solution and ammonia water into a 300 L reaction kettle, and pass nitrogen into the base solution at a rate of 0.5 m 3 / h, stir at a speed of 300 r / min to make it uniform, then heat to 60°C, control the pH value of the base solution to be 10.8-11.3, and control the ammonia concentration to be in the range of 5-7 g / L;

[0087] (3) Co-precipitation reaction: control the reaction temperature to be 60°C and the stirring speed to be 450 r / min, and perform the following stage reactions: a. Internal loose core: simultaneously flow the ammonia water, the NaOH solution and the mixed ternary metal salt solution into the reaction kettle to perform the first co-precipitation reaction, open the air to maintain the ratio of air flow to nitrogen flow at 0.2, and when the internal nucleation is completed and the particle size D50 is to 2 μm, the core is obtained, and the first stage reaction is completed; b. Intermediate dense layer: no air is passed in this reaction stage, the nitrogen is kept unobstructed, the flow rates of the ammonia water, the NaOH solution and the mixed ternary metal salt solution are increased, the ammonia water, the NaOH solution and the mixed ternary metal salt solution are simultaneously flowed into the reaction kettle to perform the second co-precipitation reaction, and when the particle size D50 grows to 6 μm, the second stage reaction is completed; c. External loose layer: open the doped metal W salt solution pump, simultaneously flow the ammonia water, the NaOH solution, the mixed ternary metal salt solution and the doped metal W salt solution into the reaction kettle to continue the third co-precipitation reaction, open the air to maintain the ratio of air flow to nitrogen flow at 0.1, and when the growth is to the target particle size D50 value of 13 μm, stop feeding the reaction;

[0088] In the first co-precipitation reaction stage of step (3), the flow rate of the mixed ternary metal salt solution is 1.5 L / h, the flow rate of the ammonia water is 150 mL / L, the flow rate of the NaOH solution is 0.5 L / h, the pH is controlled in the range of 11.0-11.2, and the ammonia is controlled in the range of 5-6 g / L;

[0089] After the first co-precipitation reaction, the flow rate of the mixed ternary metal salt solution is gradually increased to 4 L / h, the flow rate of the ammonia water is gradually increased to 300 mL / L, the flow rate of the NaOH solution is gradually increased to 1 L / h, the pH is gradually increased to 11.3-11.4, and the ammonia is controlled in the range of 5-6 g / L, and then the second co-precipitation reaction is continued under these conditions;

[0090] After the second coprecipitation reaction is completed, the third coprecipitation reaction is carried out to a stage of 40%, the pH is gradually reduced to 10.8-10.9, and the ammonia is gradually reduced to 3-4 g / L, and the third coprecipitation reaction is continued under the conditions; the flow rate of the mixed ternary metal salt solution is controlled to be 4 L / h, the flow rate of the ammonia water is controlled to be 300 mL / L, the flow rate of the NaOH solution is controlled to be 1 L / h, and the flow rate of the doped metal W salt solution is controlled to be 100 mL / h, and the doping amount of tungsten accounts for 1% of the total mole percentage of the ternary Ni, Co and Mn elements.

[0091] (4) The obtained qualified slurry is washed and dried, wherein the washing is performed twice by alkali washing and three times by water washing, the drying temperature is 100°C, and the precursor containing the radially distributed primary particles is obtained.

[0092] The embodiment also provides a preparation method of the positive electrode material, and the preparation method comprises the following steps:

[0093] The precursor prepared in step (4) and a lithium source are put into a high-speed mixer to obtain a mixture, the mole ratio of the total mole amount of nickel elements, cobalt elements, manganese elements and tungsten elements contained in the precursor to the mole amount of lithium elements contained in the lithium source is 1:1.1, and the mixture is subjected to secondary sintering in a box-type furnace, wherein the temperature of the first stage of calcination is 600°C, the time is 4h, the temperature of the second stage of calcination is 1100°C, and the time is 8h, and finally the positive electrode material is obtained.

[0094] Embodiment 4

[0095] The embodiment provides a preparation method of a precursor containing radially distributed primary particles, and the preparation method comprises the following steps:

[0096] (1) A mixed ternary metal salt solution with a total metal element concentration of 200 g / L and a mole ratio of Ni, Co and Mn elements of 80:10:10 is prepared, an NaOH solution with a mass concentration of 18% is prepared, an ammonia water with a mass concentration of 8% is prepared, and a tungsten pentachloride solution with a concentration of 50 g / L is prepared as a doped metal W salt solution;

[0097] (2) The base solution is prepared: 200 L of pure water, a certain amount of NaOH solution and ammonia water are added into a 300 L reaction kettle, nitrogen is introduced into the base solution at a rate of 2 m 3 / h, stirring is performed at a rotating speed of 300 r / min, the temperature is increased to 80°C, the pH value of the base solution is controlled to be 10.8-11.3, and the ammonia concentration is controlled to be in a range of 5-7 g / L;

[0098] (3) Coprecipitation reaction: the reaction temperature is controlled at 80°C, and the stirring speed is 450 r / min. The following stage reactions are carried out: a. Internal loose core: ammonia, NaOH solution, and mixed ternary metal salt solution are simultaneously flowed into the reactor to carry out the first coprecipitation reaction, air is opened, and the ratio of air flow to nitrogen flow is maintained at 0.05. When the internal nucleation is completed and the particle size D50 is 1.5 μm, the core is obtained, and the first stage reaction is completed; b. Intermediate dense layer: no air is passed, nitrogen is kept open, the flow rates of ammonia, NaOH solution, and mixed ternary metal salt solution are increased, ammonia, NaOH solution, and mixed ternary metal salt solution are simultaneously flowed into the reactor to carry out the second coprecipitation reaction, and when the particle size D50 grows to 4 μm, the second stage reaction is completed; c. External loose layer: the doped metal W salt solution pump is opened, ammonia, NaOH solution, mixed ternary metal salt solution, and doped metal W salt solution are simultaneously flowed into the reactor to continue the third coprecipitation reaction, air is opened, and the ratio of air flow to nitrogen flow is maintained at 0.3. When the target particle size D50 value is 11 μm, the feeding reaction is stopped.

[0099] In the first coprecipitation reaction stage of step (3), the flow rate of the mixed ternary metal salt solution is 3.5 L / h, the flow rate of ammonia is 300 mL / L, the flow rate of the NaOH solution is 1.5 L / h, the pH is controlled in the range of 11.2-11.3, and the ammonia is controlled in the range of 6-7 g / L.

[0100] After the first coprecipitation reaction is completed, to the 40% stage of the second coprecipitation reaction, the flow rate of the mixed ternary metal salt solution is gradually increased to 6 L / h, the flow rate of ammonia is gradually increased to 500 mL / L, the flow rate of the NaOH solution is gradually increased to 2.5 L / h, the pH is gradually increased to 11.4-11.6, and the ammonia is controlled in the range of 6-7 g / L. Then the second coprecipitation reaction is continued under the above conditions.

[0101] After the second coprecipitation reaction is completed, to the 40% stage of the third coprecipitation reaction, the pH is gradually decreased to 10.8-11, and the ammonia is gradually decreased to the range of 3-5 g / L. The third coprecipitation reaction is continued under the above conditions. In the third coprecipitation reaction, the flow rate of the mixed ternary metal salt solution is 6 L / h, the flow rate of ammonia is 500 mL / L, the flow rate of the NaOH solution is 2.5 L / h, the flow rate of the doped metal W salt solution is 300 mL / h, and the doping amount of tungsten accounts for 1% of the total molar percentage of the ternary Ni, Co, and Mn elements.

[0102] (4) The obtained qualified slurry is washed and dried, wherein the washing is carried out twice by alkali washing and three times by water washing, the drying temperature is 200°C, and the precursor containing the radially distributed primary particles is obtained.

[0103] The embodiment also provides a preparation method of the positive electrode material, and the preparation method comprises the following steps:

[0104] The precursor prepared in step (4) and a lithium source are put into a high-speed mixer for batch mixing to obtain a mixture, the molar ratio of the total amount of nickel element, cobalt element, manganese element and tungsten element contained in the precursor to the amount of lithium element contained in the lithium source is 1:1.1, and the mixture is subjected to secondary sintering in a box furnace, wherein the temperature of the first stage calcination is 400 DEG C, the time is 6h, the temperature of the second stage calcination is 800 DEG C, and the time is 15h, and finally the positive electrode material is obtained.

[0105] Embodiment 5

[0106] The embodiment provides a preparation method of a precursor containing primary particles distributed along a radial direction, and the preparation method is the same as that in embodiment 1, with the exception that the doping amount of tungsten accounts for 0.1% of the total molar percentage of ternary Ni, Co and Mn elements in step (3).

[0107] The embodiment also provides a preparation method of the positive electrode material, and the preparation method is the same as that in embodiment 1, with the exception that the precursor is prepared according to the embodiment.

[0108] Embodiment 6

[0109] The embodiment provides a preparation method of a precursor containing primary particles distributed along a radial direction, and the preparation method is the same as that in embodiment 1, with the exception that the doping amount of tungsten accounts for 0.5% of the total molar percentage of ternary Ni, Co and Mn elements in step (3).

[0110] The embodiment also provides a preparation method of the positive electrode material, and the preparation method is the same as that in embodiment 1, with the exception that the precursor is prepared according to the embodiment.

[0111] Embodiment 7

[0112] The embodiment provides a preparation method of a precursor containing primary particles distributed along a radial direction, and the preparation method is the same as that in embodiment 1, with the exception that the doping amount of tungsten accounts for 2% of the total molar percentage of ternary Ni, Co and Mn elements in step (3).

[0113] The embodiment also provides a preparation method of the positive electrode material, and the preparation method is the same as that in embodiment 1, with the exception that the precursor is prepared according to the embodiment.

[0114] Embodiment 8

[0115] The embodiment provides a preparation method of a precursor containing primary particles distributed in a radial direction, which is the same as that in the embodiment 1 except that the doping amount of tungsten accounts for 5% of the total mole percentage of the ternary Ni, Co and Mn elements in step (3).

[0116] The embodiment further provides a preparation method of a positive electrode material, which is the same as that in the embodiment 1 except that the precursor in the embodiment is used for preparation.

[0117] Embodiment 9

[0118] The embodiment provides a preparation method of a precursor containing primary particles distributed in a radial direction, which is the same as that in the embodiment 1 except that the feeding reaction is stopped when the target particle size D50 value is 10 microns in step (3).

[0119] The embodiment further provides a preparation method of a positive electrode material, which is the same as that in the embodiment 1 except that the precursor in the embodiment is used for preparation.

[0120] Embodiment 10

[0121] The embodiment provides a preparation method of a precursor containing primary particles distributed in a radial direction, which is the same as that in the embodiment 1 except that the feeding reaction is stopped when the target particle size D50 value is 14 microns in step (3).

[0122] The embodiment further provides a preparation method of a positive electrode material, which is the same as that in the embodiment 1 except that the precursor in the embodiment is used for preparation.

[0123] Embodiment 11

[0124] The embodiment provides a preparation method of a precursor containing primary particles distributed in a radial direction, which is the same as that in the embodiment 1 except that the first coprecipitation reaction is not connected with air in step (3).

[0125] The embodiment further provides a preparation method of a positive electrode material, which is the same as that in the embodiment 1 except that the precursor in the embodiment is used for preparation.

[0126] Comparative Example 1

[0127] The comparative example provides a preparation method of a precursor, which is the same as that in the embodiment 1 except that the doping metal W salt solution is not connected in the third coprecipitation reaction stage in step (3).

[0128] The present comparative example also provides a preparation method of a positive electrode material, which is the same as that of Example 1 except that the precursor of the present comparative example is used.

[0129] Comparative Example 2

[0130] The present comparative example provides a preparation method of a precursor, which is the same as that of Example 1 except that the pH control in the third coprecipitation reaction stage in step (3) is in the range of 11.4-11.6, the ammonia control is in the range of 5-7 g / L, and no air is introduced, but under nitrogen.

[0131] The present comparative example also provides a preparation method of a positive electrode material, which is the same as that of Example 1 except that the precursor of the present comparative example is used.

[0132] The precursors obtained in the above examples and comparative examples are used as positive electrode active materials, and are mixed with conductive carbon and PVDF at a mass ratio of 97:1.5:1.5, and then the mixture is dispersed in N-methyl pyrrolidone to obtain a positive electrode slurry. The positive electrode slurry is uniformly coated on an aluminum foil, and after coating, the current collector is punched to obtain a coin-shaped electrode. After vacuum drying at 120°C for one night, a positive electrode sheet is obtained. A metal lithium is selected as a negative electrode sheet, LiPF6 is dissolved in EC and DMC solvents (volume ratio 3:7) as an electrolyte (LiPF6 concentration is 1 mol / L), and the positive electrode sheet, the negative electrode sheet and the separator are wound to prepare a cell, and then packaged, injected, formed, and assembled into a lithium ion battery.

[0133] The lithium ion battery prepared is subjected to electrochemical performance test, and a CR2032 coin-type half cell is cycled between 3.0-4.4V (vs Li / Li + ) at 0.2C, to test the initial discharge capacity and the initial efficiency, and the discharge capacity at the 100th time, to obtain the capacity retention rate after 100 cycles. The test results are shown in Table 1:

[0134] Table 1

[0135]

[0136] From Table 1, it can be seen that:

[0137] It can be seen from Example 1 and Comparative Example 1 that the present application can effectively improve the electrochemical performance of the material by shell doping; it can be seen from Example 1 and Comparative Example 2 that the pH and ammonia value of the third co-precipitation reaction stage of the present application are smaller than those of other co-precipitation stages, and the third co-precipitation reaction stage is carried out in an air and nitrogen mixed atmosphere, so that a loose porous and primary particle size distribution shell layer can be prepared, and thus the performance of the material obtained in Comparative Example 2 is reduced; it can be seen from Example 1 and Example 2 that when the reaction conditions of each stage change, the change is gradual rather than sudden, which can further improve the matching degree between the layers and improve the performance of the material; it can be seen from Example 1 and Examples 5-8 that the doping amount of the doping element will affect the performance of the material; it can be seen from Example 1 and Examples 9-10 that when the particle size D50 after the second co-precipitation reaction is unchanged, the target particle size D50 value changes, the thickness of the outer loose layer changes, and the content of the doping element changes, thereby affecting the electrochemical performance of the material; it can be seen from Example 1 and Example 11 that the present application preferably prepares the core in an air and nitrogen mixed atmosphere, which is conducive to preparing a loose core and further improving the electrochemical performance of the material.

[0138] The above merely describes the specific embodiments of the present application, but the protection scope of the present application is not limited thereto. It should be understood by those skilled in the art that any changes or replacements within the technical scope disclosed by the present application can be easily thought of by those skilled in the art, and all such changes or replacements fall within the protection scope and disclosure scope of the present application.

Claims

1. A method of producing a precursor containing primary particles distributed in a radial direction, characterized by, The preparation method comprises the following steps: (1) introducing mixed metal source solution, complexing agent solution and precipitant solution into a bottom solution to perform a first co-precipitation reaction to obtain a core; (2) in a non-oxygen-containing protective gas, increasing the flow rates of the mixed metal source solution, the complexing agent solution and the precipitant solution to continue the second co-precipitation reaction to obtain the core coated with a dense layer; (3) in an oxygen-containing atmosphere, continuously introducing the mixed metal source solution, the complexing agent solution, the precipitant solution and a doped metal source solution to continue the third co-precipitation reaction to obtain the precursor, wherein the precursor comprises primary particles distributed in a radial direction; Preferably, after the first co-precipitation reaction in step (1) is completed, the flow rate of the mixed metal source solution is gradually increased to 4-6 L / h, the flow rate of the complexing agent solution is gradually increased to 300-500 mL / L, and the flow rate of the precipitant solution is gradually increased to 1-2.5 L / h, and then the second co-precipitation reaction is continued at the increased flow rates; 2. The production method according to claim 1, characterized by, Preferably, after the first co-precipitation reaction in step (1) is completed, the pH of the system is gradually increased to a range of 11.3-11.6, and then the second co-precipitation reaction is continued at the pH in the range of 11.3-11.

6. Preferably, after the second co-precipitation reaction in step (2) is completed, the pH of the system is gradually decreased to a range of 10.8-11, and then the third co-precipitation reaction is continued at the pH in the range of 10.8-11. Preferably, after the second co-precipitation reaction in step (2) is completed, the complexing agent concentration of the system is gradually decreased to a range of 3-5 g / L, and then the third co-precipitation reaction is continued at the complexing agent concentration of the system in the range of 3-5 g / L. The ratio of the flow rates of the air and the protective gas introduced in the first co-precipitation reaction in step (1) is 0-0.

2.

3. The production method according to claim 1 or 2, characterized by, ​ ​ ​ ​ 4. The production method according to any one of claims 1 to 3, characterized by, ​ Preferably, the particle size D50 of the core in step (1) is 1.5-2 μm; Preferably, the pH of the first co-precipitation reaction in step (1) is in the range of 11-11.3, and the complexing agent concentration is in the range of 5-7 g / L; Preferably, the flow rate of the mixed metal source solution into the bottom solution in step (1) is 1.5-3.5 L / h, the flow rate of the complexing agent solution into the bottom solution is 150-300 mL / L, and the flow rate of the precipitant solution into the bottom solution is 0.5-1.5 L / h; Preferably, the bottom solution in step (1) comprises pure water, a precipitant and a complexing agent; Preferably, the pH of the bottom solution in step (1) is 10.8-11.3, and the complexing agent concentration is 5-7 g / L.

5. The method of any one of claims 1-4, wherein, The total metal ion concentration in the mixed metal source solution in step (1), the mixed metal source solution in step (2) and the mixed metal source solution in step (3) is independently 80-200 g / L, respectively; Preferably, in the mixed metal source solution in step (1), the mixed metal source solution in step (2) and the mixed metal source solution in step (3), the molar ratio of Ni element, Co element and Mn element is independently (60-95):(0-15):(0-15), respectively; Preferably, the temperature of the first co-precipitation reaction in step (1), the second co-precipitation reaction in step (2) and the third co-precipitation reaction in step (3) is independently 50-80℃, respectively; Preferably, the particle size D50 of the core of the coated dense layer in step (2) is 4-6 μm; Preferably, the oxygen-free protective gas in step (2) comprises nitrogen; Preferably, in the second co-precipitation reaction system in step (2), the complexing agent concentration is 5-7 g / L.

6. The method of any one of claims 1-5, wherein, In the doping metal source solution in step (3), the doping metal element comprises any one or a combination of at least two of Al, Ti, Nb, Zr, W, V, Sr, Ga, Ce, Y, La, Sb or B, and is preferably W; Preferably, in the co-precipitation reaction system in step (3), the doping metal element accounts for 0.05-5% of the total molar amount of metals, and is preferably 0.5-1%; Preferably, the concentration of the doping metal source solution in step (3) is 20-50 g / L; Preferably, the oxygen-containing atmosphere in step (3) comprises air and protective gas with a flow rate ratio of 0.1-0.3; Preferably, in step (3), when the third co-precipitation reaction is performed, the flow rate of the mixed metal source solution is continuously 4-6 L / h, the flow rate of the complexing agent solution is 300-500 mL / L, the flow rate of the precipitant solution is 1-2.5 L / h, and the flow rate of the doping metal source solution is 100-300 mL / h; Preferably, in step (3), the third co-precipitation reaction is performed until a target particle size D50 is reached, and the target particle size D50 is 11-13 μm; Preferably, the chemical formula of the precursor is wherein 0.6 < a < 0.95, 0 < b < 0.15, 0 < c < 0.15, 0 < d < 0.1, a + b + c + d = 1, and M comprises any one or a combination of at least two of Al, Ti, Nb, Zr, W, V, Sr, Ga, Ce, Y, La, Sb, or B.

7. A precursor comprising primary particles distributed in a radial direction, characterized in that, The precursor containing radially distributed primary particles is prepared by the preparation method of any one of claims 1-6; The precursor containing radially distributed primary particles comprises a core, a dense layer on the surface of the core, and a loose layer on the surface of the dense layer.

8. A positive electrode material, characterized by, The positive electrode material is obtained by mixing and sintering a lithium source and the precursor containing radially distributed primary particles as claimed in claim 7.

9. The positive electrode material of claim 8, wherein, The molar ratio of total metal ions in the precursor containing radially distributed primary particles to lithium ions in the lithium source is 1:(1.1-1.2). Preferably, the sintering comprises a first sintering stage and a second sintering stage performed in sequence, wherein the first sintering stage has a temperature of 400-600℃, a time of 4-6h, and a temperature rising speed of 2-5℃ / min, and the second sintering stage has a temperature of 800-1100℃, a time of 8-15h, and a temperature rising speed of 4-8℃ / min.

10. A lithium-ion battery, characterized by, The lithium ion battery comprises the positive electrode material as claimed in claim 8 or 9.